2019
DOI: 10.1016/j.jtho.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cranial Irradiation for Limited-Stage Small-Cell Lung Cancer Patients: Secondary Findings From the Prospective Randomized Phase 3 CONVERT Trial

Abstract: Introduction: The impact of the dose and fractionation of thoracic radiotherapy on the risk of developing brain metastasis (BM) has not been evaluated prospectively in limited stage SCLC patients receiving prophylactic cerebral irradiation (PCI).Methods: Data from patients treated with PCI from the CONVERT trial were analyzed.Results: Four hundred forty-nine of 547 patients (82%) received PCI after completion of chemoradiotherapy. Baseline brain imaging consisted of computed tomographic scans in 356 of 449 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…For one, this was a retrospective study that is susceptible to selection bias. In addition, certain known prognostic parameters were not incorporated into our analyses, including thoracic gross tumor volume, tumor size, maximum PET standardized uptake values (SUVmax), vascular invasion, or perineural invasion [24,25]. Similarly, certain relevant molecular factors such as anaplastic lymphoma kinase-rearranged and ROS1-rearranged were not assessed [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, this was a retrospective study that is susceptible to selection bias. In addition, certain known prognostic parameters were not incorporated into our analyses, including thoracic gross tumor volume, tumor size, maximum PET standardized uptake values (SUVmax), vascular invasion, or perineural invasion [24,25]. Similarly, certain relevant molecular factors such as anaplastic lymphoma kinase-rearranged and ROS1-rearranged were not assessed [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…While lung SRCC (LSRCC) primary tumors are extremely rare, they do occur, and were first proposed as a unique disease entity with specific clinicopathological characteristics and a poor prognosis by Kish et al in 1989 [6]. One study of 24,171 SRCC patients found that just 3.1% of these cases originated in the lungs [7]. Multivariate analyses revealed LSRCC to have comparable cause-specific survival to that of gastric SRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays MRI is available and its introduction has increased the detection of brain metastases from 10% to 24% (13). However, in a recent published trial conducted between 2008 and 2013 baseline imaging of the brain was still done by CT scan in 79% of the 449 patients (14). Furthermore, patients detected with brain metastases through CT had symptoms while they were asymptomatic in case of MRI.…”
Section: Impact Of Brain Imagingmentioning
confidence: 99%
“…Small cell lung cancer (SCLC) is an exceptionally lethal cancer for which new therapeutic approaches are needed. Despite over 30 years of clinical research, little progress has been made in the management of SCLC, and outcomes remain poor with median overall survival (OS) of 29 months with chemo-radiotherapy and prophylactic cranial irradiation in limited stage SCLC, and of 9-11 months in the metastatic setting with platinumetoposide, even in the most recent randomized clinical trials with chemotherapy alone (1,2). Owing to the short-term clinical benefit of chemotherapy in SCLC, an understanding of the molecular basis of the onset of chemotherapy resistance in this population is easily awaited, as this could trigger the development of new treatment strategies, and help to identify potential druggable genomic alterations.…”
mentioning
confidence: 99%